FORECASTING PERSEDIAAN STOK TOKO REZA SUKSES DENGAN METODE DES - eka eka; William Ramdhan; Wan Mariatul Kifti inti (Program Studi Sistem Informasi, Universitas Banten Jaya, 2026)
The development of information technology offers significant opportunities for businesses to improve operational efficiency, including inventory management. Toko Reza Sukses, a clothing retail business, faces challenges in balancing stock levels with customer demand. This imbalance can lead to overstocking or stockouts, resulting in losses and decreased customer satisfaction. This study aims to apply the Double Exponential Smoothing (DES) method to forecast stock requirements based on historical data. DES was chosen for its ability to capture upward or downward trends in sales data. The system is designed as a web-based application using the PHP programming language to facilitate an effective and efficient forecasting process. The implementation results show that the system is capable of providing more accurate stock estimates, reducing instances of stock shortages and surpluses, and enhancing customer satisfaction through better product availability.